Men with Adult Onset Epileptic Seizures: Their Coping Strategies and Sense of Subjective Wellbeing following Elective Neurosurgery. Issue 1 (21st March 2017) - Raffaele, Martin; Mpofu, Elias; Smith-Merry, Jennifer; Mackey, Martin
Abstract : This study aimed to understand the coping strategies used by men with Adult Onset Epileptic Seizures (AOES) following elective neurosurgery, and in particular, how those adaptive skills relate to their subjective wellbeing (SWB). Open-ended qualitative interviews were conducted with five men with a history of neurosurgery for AOES (aged 34–59). The interview data was thematically analysed utilising interpretive phenomenological analysis. The findings indicated that the men experienced significant role marginalisation by family and co-workers, and also poor communication provided by health care professionals. They reported a higher sense of SWB with the use of ego-buffering strategies, such as positive reframing, threat minimisation, emotional self-acceptance and engaging in wish-fulfilling fantasies. Self-blame led to lower SWB. Findings imply that agentic behaviour is important to successful living with AOES following neurosurgery.